THE REPUBLIC OF TAJIKISTAN AND THE ISLAMIC REPUBLIC OF IRAN: COOPERATION ACHIEVEMENTS AND PROSPECTS - Dodikhudoev, Khurshed; Niyatbekov, Vafo (CENTRAL ASIA AND THE CAUCASUS, 2008)
Diplomacy in independent Tajikistan seeks to develop relations with all the members of the world community. Moreover, the multi-vector nature of its foreign policy is also conducive to establishing priority cooperation with those countries with which stronger ties are mutually beneficial. Recently, many states have acquired the label of “regional power.” This term applies to those countries whose influence is not limited to only one theater of political, economic, and humanitarian activity. Whereby in a particular region, such states may have enough potential to directly affect the current political processes. Although this term is not new (it has been in circulation for more than fifty years), it has become increasingly popular over the last 10-15 years as those states that fit this category have become more active. Today, one such state in the region is Iran. The influence of this country on current regional processes has perceptibly grown recently, which makes it possible to regard Iran as one of the sustainably developing regional powers. After the formation of the U.S.S.R., Iran’s political, economic, and cultural influence in Central Asia dwindled to nothing, but it always tried to retain its niche in the region even in Soviet times. Official Tehran’s initiative to move its consulate from Leningrad (St. Petersburg) to Dushanbe in 1980 did not escape public attention. However, the Soviet authorities did not support the Iranian leadership’s proposal at that time. Iran is one of the four countries bordering on Central Asia, along with the Russian Federation, the People’s Republic of China, and the Islamic State of Afghanistan. The appearance of five newly independent states attracted increased attention from the Iranian political establishment, which was manifested over time in specific projects that allowed Tehran to perceptibly reinforce its……………….